Efficiency of casein phosphopeptide amorphous calcium phosphate versus topical fluorides on remineralizing early enamel carious lesions - A systematic review and meta analysis - P. Rahmath Meeral; Srisakthi Doraikannan; Meignana Arumugham Indiran (Elsevier, 2024)
Objective: To assess the remineralizing efficiency of caesin phosphopepdide amorphous calcium phosphate (CPP-ACP) versus topical fluorides on early enamel lesions in vivo. Data sources: PubMed, Web of Science, Scopus, EBSCO were searched based on the PICOS criteria up to December 2022 with English language restriction. All relevant studies were subjected to two separate reviews before being included at the title, abstract, and full text levels. Study selection: 41 studies were reviewed and 11 selected for inclusion in the final sample for the review. All were randomized clinical trials with the follow-up period of the studies ranging from 3 to 12 months. Out of the 11 studies, only two are with low risk of bias on assessment with Cochrane risk of bias assessment tool, while the other nine articles were with the moderate and high risk of bias. Conclusions: Conflicting evidence exists on the clinical efficacy of CPP-ACP compared to the various fluoride forms tested, and no adverse effect associated with CPP-ACP use was discovered in comparison to fluorides that had certain detrimental health impacts. Although, the review results in favor of both fluorides and CPP-ACP with similar clinical efficiency, when ill effects are considered the CPP-ACP can be a choice of remineralizing early enamel lesions. However, before concrete suggestions can be given, high-quality, well-designed clinical research in this area are still necessary. Clinical significance: A considerable remineralizing impact has been shown in both in vitro and in vivo experiments, making CPP-ACP/CPP-ACPF a more promising remineralizing agent than fluorides. Therefore, this can be applied clinically to early enamel carious lesion.